2006
DOI: 10.3201/eid1206.051258
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant CommensalEscherichia coliin Children, Peru and Bolivia

Abstract: Healthy children in urban areas have a high prevalence of fecal carriage of drug-resistant E. coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
122
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(140 citation statements)
references
References 21 publications
11
122
1
5
Order By: Relevance
“…According to our study, the fi rst line antibiotics to be used for the treatment of UTI is nitrofurantoin. In our study, we defi ned those organisms as MDR which were resistant to two or more diff erent structural classes of antibiotics 6 . According to this, 33 (55.0%) MDR isolates were detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our study, the fi rst line antibiotics to be used for the treatment of UTI is nitrofurantoin. In our study, we defi ned those organisms as MDR which were resistant to two or more diff erent structural classes of antibiotics 6 . According to this, 33 (55.0%) MDR isolates were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistance is defi ned as resistance to two or more diff erent structural classes of antimicrobial agents 6 . There is growing concern regarding the resistance to uropathogens to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Increased E. coli [43][44][45][46] and Streptococcus pneumoniae 9,[47][48][49] resistance in younger children generally have been attributed to greater antibiotics use by these children, [43][44][45][46][47] although one study cautioned that this could not be true for quinolone resistance because this drug was not used in their youngest age group. 46 Many investigators lacked data on their subjects' antibiotics use, and only two 9, 45 examined use and age together in a multivariable analysis. Although both found that younger age and greater use were independent risk factors for resistance, they hypothesized that younger age increased risk through elevated use.…”
Section: Discussionmentioning
confidence: 99%
“…to 0.5 McFarland turbidity standard and mixed in a sterile test tube at the ratio of 1 to 10 (donor to recipient) and incubated at 37°C for 14 h (Bartoloni et al, 2006). After incubation, samples (0.1 ml) were spread onto the surfaces of Nutrient and MacConkey agar plates supplemented with nalidixic acid (30 μg/ml).…”
Section: Plasmid Transfermentioning
confidence: 99%